Enhancing Community Empowerment and Capacity Through Collaboration With The Fajar Laut Group in Padangdangan Sumenep - Alfisuma, Meria Zakiyah; Laksani, Mertiara Ratih Terry; Cahya, Ilham; Syah, Ach. Fachruddin (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
Local fishermen in Padangdangan Village still rely on traditional methods to determine fishing areas, which are less effective due to the dynamic changes in marine ecosystems. Additionally, the community faces other challenges, including a lack of knowledge in fish processing, low awareness of the importance of halal certification for UMKM products, and limited digital marketing strategies. Therefore, this community engagement program aims to improve community welfare through community-based education. The method used in this activity is Community-Based Research (CBR), which actively involves the community in problem identification, program planning, implementation, and evaluation. This program consists of four main activities: oceanography-based fishing area determination education, fish handling and processing training, halal certification counseling for MSME products, and digital marketing training. The results of the program show that fishermen have gained new insights into scientific techniques for determining fishing areas, contributing to increased catches and marine ecosystem sustainability. Additionally, the community has acquired skills in fish processing to enhance product value, understood the importance of halal certification for their products, and mastered digital marketing techniques to expand market reach. In conclusion, this program has successfully provided tangible benefits to the people of Padangdangan Village, improving their economic and social well-being through educational and participatory approaches.